2022
DOI: 10.1111/jfbc.14206
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic cardiomyopathy was attenuated by cinnamon treatment through the inhibition of fibro‐inflammatory response and ventricular hypertrophy in diabetic rats

Abstract: Diabetic cardiomyopathy (DCM) is a chronic complication of diabetes that emphasizes the urgency of developing new drug therapies. With an illustrious history in traditional medicine to improve diabetes, cinnamon has been shown to possess blood lipids lowering effects and antioxidative and anti‐inflammatory properties. However, the extent to which it protects the diabetic heart has yet to be determined. Forty‐eight rats were administered in the study and grouped as: control; diabetic; diabetic rats given 100, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…Cell membrane damage and increased permeability can cause the leakage of CK‐MB and LDH. LDH and CK‐MB are well‐known biomarkers for cardiac damage 31 . The study found that diabetes induction elevated the levels of the diagnostic marker enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Cell membrane damage and increased permeability can cause the leakage of CK‐MB and LDH. LDH and CK‐MB are well‐known biomarkers for cardiac damage 31 . The study found that diabetes induction elevated the levels of the diagnostic marker enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…Being one of the common metabolic disorders affecting various body organs and the leading cause of death globally, DM attracts researcher interest and curiosity [30]. Diabetes and testicular injury are interlinked disorders affecting male fertility [31].…”
Section: Discussionmentioning
confidence: 99%
“…The blood pressure of normal rats (baseline blood pressure) was recorded, and subsequently hypertension was induced in both hypertensive control group and cinnamon group by oral administration of L-NAME 40 mg/kg daily for two weeks ( Adaramoye et al, 2012 , Adedapo et al, 2020 , Ahad et al, 2022 , Alam et al, 2021 , Alam et al, 2020 , Metchi Donfack et al, 2021 , Sung et al, 2013 ). The cinnamon group received oral dose of cinnamon 200 mg/kg daily for two weeks in addition to L-NAME ( Abdeen et al, 2019 , Farazandeh et al, 2022 , Jain et al, 2015 , Sayad-Fathi et al, 2020 , Sharafeldin and Rizvi, 2015 ). After two weeks, the measurement of animal blood pressure was conducted by Visitech tail-cuff system (Visitech, BP-2000 Series II, USA) at 0, 1, 2, 4, 8, 12, 24 h ( Ahad et al 2022 ).…”
Section: Methodsmentioning
confidence: 99%